Errors on the pre-Trial Investigation: Legal Nature and Causes - SYRLYBAYEV, Marat; AUBAKIROVA, Anna Alexandrovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Successful pre-trial investigation of criminal offenses is impossible without timely and effective decision-making process and the conduct of investigations. It was in the course of the investigation forms the basis of the evidence base for criminal cases. The results of investigative actions directly affect the level of quality basic tasks of criminal proceedings – Protection of rights and legitimate interests of individuals and organizations, victims of crime and the protection of individuals from illegal and unwarranted accusation, conviction and restriction of rights and freedoms. In practice, crime investigation to identify positive and negative experiences, progressive, regressive, and be distributed to be corrected - error. In this paper, the author reviewed some issues of improving the investigative practices, improve the quality of pre-trial investigation of criminal cases, the rule of law in the work of the prosecution and the principles of criminal procedure. The definition of the legal nature, the timely removal of gaps and errors enable necessarily increase the sense of justice and official responsibility of officials, as well as law-abiding citizens to strengthen faith in the justice of actions of the executive authority in the field.
Keywords: criminal law; pre-trial investigation; criminal prosecution authorities; the legal nature of; reasons for investigating the error; improving investigative practices; gaps and shortcomings elimination